Journal of Spacecraft Technology: A Bibliometric Study - Malathy, S.; Kantha, P. (Journal of Information and Knowledge, 2015)
Journal of Spacecraft and Technology, an in-house publication of ISRO Satellite Centre publishes the research activity of the centre. This paper presents bibliometric study of the journal published during 1991 to 2012, which includes 22 volumes with 330 papers and 2597 citations. The analysis was made on different parameters like year-wise distribution of articles for the period of study (1991-2012), length of articles, authorship pattern of contributions, author productivity, degree of collaboration among co-authors and gender-wise distribution of papers. It also presents Institution-wise contribution, group-wise (only ISAC) contribution, ranked list of prolific/productive authors, number of citations appeared in papers and form-wise distribution of citations. This study provides the insight and development of the journal towards excellence.